Zeeman deceleration beyond periodic phase space stability - Toscano, J (University of Oxford, 2017)
Raw data, simulations and analysis code for the evidence presented in the paper "Zeeman deceleration beyond periodic phase space stability" by Jutta Toscano, Atreju Tauschinsky, Katrin Dulitz, Christopher J. Rennick, Brianna R. Heazlewood and Timothy P. Softley published in New J. Phys. 19 (2017) 083016.